2013
DOI: 10.1179/1476830513y.0000000087
|View full text |Cite
|
Sign up to set email alerts
|

Dietary omega-3 deficiency reduces BDNF content and activation NMDA receptor and Fyn in dorsal hippocampus: Implications on persistence of long-term memory in rats

Abstract: Omega-3 (n-3) fatty acids are important for adequate brain function and cognition. The aim of the present study was to evaluate how n-3 fatty acids influence the persistence of long-term memory (LTM) in an aversive memory task and to explore the putative mechanism involved. Female rats received isocaloric diets that included n-3 (n-3 group) or not (D group). The adult litters were subjected to an inhibitory avoidance task (0.7 mA, 1.0 seconds foot shock) to elicit persistent LTM. Twelve hours after the trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…As suggested by previous studies, a diet rich in omega‐3 fatty acids supports cognitive processes in humans and positively regulates genes that are important for the maintenance of synaptic function and plasticity in rodents . Previous studies have suggested that a dietary deprivation of omega‐3 fatty acids in rodents results in reduced BDNF and trkB levels in the striatum, frontal cortex, and hippocampus . The strong nutritional differences between an egg white diet and an egg yolk diet implies that shifting from an egg yolk diet to an egg white one may have dramatic consequences for brain performance.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As suggested by previous studies, a diet rich in omega‐3 fatty acids supports cognitive processes in humans and positively regulates genes that are important for the maintenance of synaptic function and plasticity in rodents . Previous studies have suggested that a dietary deprivation of omega‐3 fatty acids in rodents results in reduced BDNF and trkB levels in the striatum, frontal cortex, and hippocampus . The strong nutritional differences between an egg white diet and an egg yolk diet implies that shifting from an egg yolk diet to an egg white one may have dramatic consequences for brain performance.…”
Section: Discussionmentioning
confidence: 90%
“…37 Previous studies have suggested that a dietary deprivation of omega-3 fatty acids in rodents results in reduced BDNF and trkB levels in the striatum, 33 frontal cortex, 37 and hippocampus. 38 The strong nutritional differences between an egg white diet and an egg yolk diet implies that shifting from an egg yolk diet to an egg white one may have dramatic consequences for brain performance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to investigating the neurological development of newborns, the present study also evaluated the influence of cashew nuts on memory tasks, as adequate amounts of LC-PUFA provide integrity of cell membranes and form myelin on neurons and glia cells, being fundamental to ensure normal brain function in individuals for learning and cognition (Yehuda et al, 2006;Soares et al, 2009). Memory acquisition is a process involving molecular and cellular events activated immediately after the training session and after a few hours to a few days of the task, occurring in specific brain regions such as the hippocampus (Bekinschtein et al, 2010;Medina et al, 2008;Bach et al, 2014). Neurogenesis especially occurs in the dentate gyrus of the hippocampus, where recently formed neurons are recruited to pre-existing neural circuits, being involved in the hippocampus-dependent learning processes (Drapeau et al, 2003;Fernandes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive reports using rodent models have identified that deficiency of DHA during growth and development causes significant learning and memory impairments [2, 9–12]. In addition to being critical for brain development [1317] dietary DHA is particularly important during challenging situations such as aging [1821], or brain injury [22, 23].…”
Section: Introductionmentioning
confidence: 99%